A Bibliometric Analysis of Citation Classics in the Journal of Ultrasound in Medicine. (16th January 2020) - Balica, Adrian; Kohut, Adrian; Tsai, Te‐Jung; Groszmann, Yvette S.; Brandt, Justin S.
Abstract : Objectives: A bibliometric analysis of articles in the Journal of Ultrasound in Medicine ( JUM ) identified the journals' most impactful articles. Methods: A bibliometric analysis of citation classics that were published in the JUM from its inception in 1982 to 2019 was performed. All citation classics, defined as articles cited 100 or more times, were evaluated for the number of citations, citations per year, publication year, subspecialty, design, and country of origin. Characteristics were compared before and after 1998 by the Mann‐Whitney test for unpaired data and 2‐sample z tests of sample proportions. The Kruskal‐Wallis test for nonparametric continuous data was used to compare the median number of citations per year by decade of publication. Results: A total of 7868 articles were published in the JUM between 1982 and 2019; 54 (0.7%) were citation classics. The median citation classics year of publication was 1998 (interquartile range [IQR], 1991–2003). Most citation classics originated from the United States (36 of 54 [66.7%]), were observational (47 of 54 [87%]), and were related to obstetric and gynecologic topics (16 of 54 [29.6%]). Citation classics after 1998 received significantly more citations per year (9.3 versus 4.7; P < .001), with no other differences noted. The median number of citations per year increased for each decade, with medians of 4 citations (IQR, 3.6–4.7) in 1982 to 1991 and 11.2 citations (IQR, 9–13.9) in 2002 to 2012 ( P < .001). Conclusions: This list provides insight into the most influential articles that were published in the JUM . Most citation classics were observational, were from the United States, and covered obstetric and gynecologic topics. Citation classics received more citations per year after 1998.